No difference in surgical time and total theatre time between robotically assisted and computer assisted total knee arthroplasty - David Johannes Haslhofer; Victoria Anelli-Monti; Peter Hausbrandt; Christian Kammerlander; Antonio Klasan (Journal of Orthopaedics and Traumatology)
Abstract Introduction A number of studies have demonstrated a significant reduction of surgical time for robotically assisted surgery (RAS) total knee arthroplasty (TKA) after the learning curve between 6 and 43 cases. It is unknown if the logistics of RAS produce a longer total theatre time since published literature only reflects the surgical time. It is also unknown how RAS surgical and total theatre times compare with computer assisted surgery (CAS) TKA. Methods This is a prospective study of 524 consecutive patients undergoing a CAS or a RAS TKA using the same cementless implant. We recorded age, sex, body mass index (BMI), incision time of the first case, total surgical time, total theatre time, length of stay and 90-day complication and readmission rate. Results During the study period, 205 CAS and 199 RAS TKA were performed. There was no difference at baseline in age (p = 0.546), sex (p = 0.920) or BMI (p = 0.791). Surgical time for CAS was 78.3 (± 22.2) min and for RAS was 80.1 (± 25.7) min, p = 0.451. Total theatre time for CAS was 117.4 (± 27.8) min and 119.3 (± 30.7) min for RAS, p = 0.515. There was no difference in length of stay (p = 0.674), 90-day complication (p = 0.530) or readmission rate (p = 0.930). There was a difference in skin-incision average time for the first case (p = 0.022). Conclusions Although theatre set-up for the first case is 5 min longer, RAS-TKA does not prolong the surgical time or total theatre time when compared with CAS-TKA. There was no reduction in case volume since the introduction of robotics. Level of evidence III.